2022
DOI: 10.3847/1538-4357/ac82ef
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-Ray Polarization Catalog for a Five-year Sample of Gamma-Ray Bursts Using AstroSat CZT Imager

Abstract: The Cadmium Zinc Telluride Imager (CZTI) on board AstroSat has been regularly detecting gamma-ray bursts (GRBs) since its launch in 2015. Its sensitivity to polarization measurements at energies above 100 keV allows CZTI to attempt spectropolarimetric studies of GRBs. Here, we present the first catalog of GRB polarization measurements made by CZTI during its first five years of operation. This includes the time-integrated polarization measurements of the prompt emission of 20 GRBs in the energy range 100–600 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…We also verified that both the modulation curve fitting method and template fitting method yield similar results, particularly when the number of Compton events is limited as in case of CZTI GRBs. This further validates the methods and results reported in Chattopadhyay et al (2019) 37 and Chattopadhyay et al (2022) 38 for GRB prompt emission.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also verified that both the modulation curve fitting method and template fitting method yield similar results, particularly when the number of Compton events is limited as in case of CZTI GRBs. This further validates the methods and results reported in Chattopadhyay et al (2019) 37 and Chattopadhyay et al (2022) 38 for GRB prompt emission.…”
Section: Discussionsupporting
confidence: 91%
“…In the analysis of experimental ASADs, we had to account for charge sharing effect. Chattopadhyay et al (2022), 38 for a sample of twenty bright GRBs, showed that the ratio of Compton to Single Pixel events is consistently higher in experimental data than in simulation results (see Figure 1 of Chattopadhyay et al, 2022 38 ). This effect is attributed to charge sharing between the adjacent pixels which can mimic a Compton event and consequently add to the number of true Compton events.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations